Kompetensi Mahasiswa PGPAUD Sebagai Calon Guru Pada Program P3K UPI - Nurfidanova, Yulia; Sianturi, Risbon; Hendri Mulyana, Edi (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2025)
Teachers play a central role in determining the success of education, especially at the early childhood education level. In facing the challenges of the 21st century, which demand digital literacy and increasingly complex professional competencies, prospective early childhood education teachers (PAUD) need to be comprehensively prepared through educational programs that integrate theory and practice. This study aims to describe the competency levels of PGPAUD students at Universitas Pendidikan Indonesia during their participation in the Professional Education Strengthening Program (P3K). The research employs a quantitative approach with a descriptive method, and the data were analyzed using frequency tabulation to illustrate the distribution. The sample consists of 191 students selected through proportional random sampling. The research instrument used was a Likert scale questionnaire measuring three key aspects of competence: knowledge, skills, and attitudes. The results showed that 53.40% of students fell into the very high category and 46.60% into the high category, with no respondents in the medium, low, or very low categories. These findings indicate that PGPAUD UPI students possess strong competencies as prospective professional teachers ready to meet the demands of 21st-century education. The theoretical contribution of this study reinforces Mulyasa’s theory of teacher competence, which emphasizes the importance of mastery in knowledge, skills, and attitudes as the main pillars of teacher competence. Practically, the results of this study can serve as an evaluation and continuous improvement tool for the curriculum and implementation of the P3K Program, thereby better preparing PGPAUD students to become professional, adaptive, and innovative teachers